Multiple Myeloma Cells Express Key Immunoregulatory Cytokines and Modulate the Monocyte Migratory Response - Freire-de-Lima, Leonardo; Nardy, Ana Flávia Fernandes Ribas; Ramos-Junior, Erivan Schnaider; Conde, Luciana; Santos Lemos, Jéssica; Fonseca, Leonardo Marques da; Lima, Juliana Echevarria; Maiolino, Angelo; Morrot, Alexandre (Frontiers in Medicine, 2017)
Multiple Myeloma (MM) is a plasma-cell disorder that still remains incurable. The immune dysfunction of the host is a striking characteristic of MM, leading to tumor growth and reducing the survival rate of patients. Monocytes are precursors of conventional dendritic cells (DC), a major player in the immunity mechanisms driving protective T cell responses against tumor. Herein, we report that human MM RPMI 8226 cell line shows an pronounced chemoattractant activity for monocytes and also expresses enhanced levels of the leukocyte chemotactic cytokines CXCL12, CCL5, MIP-1β and CXCL10 in association with elevated levels of both key immunoregulatory interleukins such as IL-4 and IL-10. This cytokine profile was observed together with reduced expression of IFN-γ by MM RPMI 8226 cell line, a determinant interleukin involved in the acquisition of cellular-mediated protective responses against tumor cells. We further demonstrate that MM RPMI 8226 cell line expresses elevated levels of soluble form of the intercellular adhesion molecule ICAM-1 known to inhibit anti-tumoral T cell responses. This attractive modulation of immune responses by MM cells might provide a means to impair early anti-tumor responses during the establishment of cytokine-mediated immunosuppressive tumor niche.